Liturgical inculturation or liberation? A qualitative exploration of major themes in liturgical reform in South Africa - Wepener, Cas (HTS teologiese studies, 2014)
In this article, the notion of liturgical inculturation is revisited in the light of qualitative liturgical research conducted in local faith communities as well as with church leaders in South Africa regarding liturgical reform over recent decades. Two central themes were identified as representing important changes that occurred and are still occurring in the liturgy in South Africa roughly since Vatican II and the promulgation of Sacrosanctum Concilium. They are referred to here as ‘the language of women’ and ‘the language of justice’. The concept of liturgical inculturation is revisited in the light of the ways in which these two ‘languages’ function and functioned in the liturgies of churches in South Africa. In conclusion, an argument is advanced for a more comprehensive understanding of the notion of liturgical inculturation in order to assist the liturgy to regain its prophetic voice in South Africa today.